2004
DOI: 10.5688/aj680368
|View full text |Cite
|
Sign up to set email alerts
|

Drug Information Questions Posed to Community Pharmacy Advanced Practice Experience Students

Abstract: Outcomes includes the provision of drug information to health care professionals and the public as one of the many outcomes pharmacy graduates should have mastered upon completion of the curriculum. 1 Due to their accessibility, community pharmacists receive numerous drug information questions from patients. Therefore, the ability to evaluate a health-related inquiry and provide an appropriate response to the requestor in a community pharmacy setting is an essential skill to develop. Faculty members should ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…However, little research has been conducted to determine the nature of medicine‐related questions that community pharmacies handle, nor the validity of the responses 6 . Research data relating to medicine call handling seem to be limited to specialist services 7 or national drug information centres 8 …”
Section: Introductionmentioning
confidence: 99%
“…However, little research has been conducted to determine the nature of medicine‐related questions that community pharmacies handle, nor the validity of the responses 6 . Research data relating to medicine call handling seem to be limited to specialist services 7 or national drug information centres 8 …”
Section: Introductionmentioning
confidence: 99%
“…Study results indicated questions from consumers were most likely to be classified as adverse drug reactions, while questions from health professionals were likely to be classified as dosage and drug administration. 8 A survey of 162 community and independent pharmacies in Louisiana reported nonprescription medications, adverse drug reactions, and contraindications/warning questions as the top 3 types of questions received from the public and other health professionals. 10 Comparison of the characteristics of communitybased drug information questions obtained from the present survey and characteristics of questions received at an academic drug information center revealed notable differences.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Investigators of a recently published study evaluated the types of questions received by pharmacy students completing an APPE in community pharmacy; however, some of the questions received by the students participating in the study were contrived for the practice experience and may not reflect true consumer-based questions. 8 To our knowledge no comparative analysis has been published in the literature examining potential differences between academic training and career experiences in drug information. Therefore, the primary objective of the present study was to determine the characteristics of communitybased drug information requests compared to requests received at an academic drug information center.…”
Section: Introductionmentioning
confidence: 99%
“…35 Additionally, an evaluation of drug information questions answered during community advanced pharmacy practice experiences were evaluated to determine the types of questions asked and the resources students used to answer those questions. 36 These data were used to enhance curricular development of the needed skills earlier in the curriculum and to determine the availability of the resources needed to answer the questions posed by patients and health care professionals.…”
Section: Pharmacy Practice Experience Evaluations and Activitiesmentioning
confidence: 99%